Plea Bargaining and Indonesia’s Special Track Under The New KUHAP: A Comparative Study with United State - Sapanah, Mawar; Lewoleba, Kayus Kayowuan (Universitas Islam Negeri Alauddin Makassar, 2026)
The increase in criminal cases, the length of the judicial process, and the overcrowding of correctional institutions have prompted the need for reform of criminal procedure law in Indonesia. One of the breakthroughs adopted in the New Criminal Procedure Code (KUHAP) is the mechanism of guilty pleas through the Special Track, which is conceptually similar to plea bargaining as applied in the United States criminal justice system. This study aims to analyze the comparison between the plea bargaining mechanism in the United States and the Special Track in Indonesia's New KUHAP, as well as to examine the implications of adopting elements of plea bargaining on the protection of the principle of due process of law and the application of the principles of swift, simple, and inexpensive justice. The research method used is normative juridical with a legislative, comparative, and conceptual approach, supported by a literature study of primary, secondary, and tertiary legal materials. The results of the study show that although both mechanisms have the same objective, namely the efficient resolution of criminal cases, there are fundamental differences in their structure, scope of negotiation, and the role of judges. The Special Track in the New Criminal Procedure Code places judges as the main controllers of the guilty plea process, thereby potentially strengthening the protection of due process of law. However, without clear technical regulations and strict judicial oversight, this mechanism risks putting pressure on defendants and reducing their right to a fair trial.